Draft mitochondrial genomes of Hirudo medicinalis and Hirudo verbana (Annelida, Hirudinea). Issue 1 (1st January 2016) - Nikitina, Anastasia; Babenko, Vladislav; Akopian, Tatyana; Shirokov, Dmitriy; Manuvera, Valentin; Kurdyumov, Alexey; Kostryukova, Elena; Lazarev, Vassili
Abstract: Here we present two incomplete mitochondrial genome sequences of Hirudo medicinalis and Hirudo verbana (Annelida, Hirudinea). The corresponding sequences are 14, 729 and 14, 604 base pairs in length. They contain all mitochondrial genes (13 protein-coding genes, 22 tRNAs and two rRNAs) but lack the non-coding region. Nevertheless, the robust reconstruction of their phylogenetic relationships presented here reveals distinct separation of both leeches from other annelids and at the same time relatively high dissimilarity between each other.